Polymers As Concrete Healing Materials - Gorur, Mesut (Journal of Composites and Biodegradable Polymers, 2023)
Concrete is commonly used as a supporting material in the construction industry. Although it can withstand heavy loads, it is very brittle and sensitive to crack formation. Earthquakes and other environmental factors may result in the formation of cracks in the concrete structure. Penetration of chloride and atmospheric water with dissolved oxygen and carbon dioxide gasses through these cracks leads to corrosion of rebar (reinforcing steel bars). This paper is a short review of polymeric structures as concrete healing materials.